Single-molecule junctions map the interplay between electrons and chirality - Anil-Kumar Singh; Kévin Martin; Maurizio Mastropasqua Talamo; Axel Houssin; Nicolas Vanthuyne; Narcis Avarvari; Oren Tal (Nature Communications)
Abstract The interplay of electrons with a chiral medium has a diverse impact across science and technology, influencing drug separation, chemical reactions, and electronic transport1-30. In particular, electron-chirality interactions can significantly affect charge and spin transport in chiral conductors, making them highly appealing for spintronics. However, an atomistic mapping of different electron-chirality interactions remains elusive. Here, we find that helicene-based single-molecule junctions behave as a combined magnetic-diode and spin-valve device. This dual-functionality enables the identification of an atomic-scale coexistence of different electron-chirality interactions: the magnetic-diode behavior is attributed to an interaction between electron’s angular momentum in a chiral medium and magnetic fields, whereas the spin-valve functionality is ascribed to an interaction between the electron’s spin and a chiral medium. This work uncovers the coexistence of electron-chirality interactions at the atomic-scale, identifies their distinct properties, and demonstrates how integrating their functionalities can broaden of the available methods for spintronics.